2014
DOI: 10.1007/s12206-014-1040-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of alumina on mechanical and tribological characteristics of graphite particle reinforced hybrid Al-MMC

Abstract: We consider the influence of alumina (Al 2 O 3 ) particles on mechanical and tribological properties of aluminum hybrid metal matrix composites (MMC). Various weight fraction of Al 2 O 3 (5, 10 and 15%) and constant weight fraction of graphite (5%) were used to fabricate composites by stir casting method. The effect of Al 2 O 3 content on hardness, density and specific wear rate is evaluated. A wear test was performed using central composite design matrix on a pin-on disc apparatus at room temperature for cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In a similar study, Alaname and Sanusi [25] reported that hybrid composite materials containing graphite had better wear resistance than composite materials without graphite, while increased graphite ratio reduced wear resistance. Also, Premnath et al [26] in a similar study they conducted, they investigated the mechanical and tribological behavior of AMCs reinforced 5% by graphite and by 5%, 10% and 15% Al2O3 within Al matrix. In their results, they stated that the reinforcement amount is the dominating parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study, Alaname and Sanusi [25] reported that hybrid composite materials containing graphite had better wear resistance than composite materials without graphite, while increased graphite ratio reduced wear resistance. Also, Premnath et al [26] in a similar study they conducted, they investigated the mechanical and tribological behavior of AMCs reinforced 5% by graphite and by 5%, 10% and 15% Al2O3 within Al matrix. In their results, they stated that the reinforcement amount is the dominating parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the AMMCs can be tailored according to the specific application requirements by the appropriate selection of matrix, reinforcement and the fabrication process (Radhika and Subramanian 2013;Sharma et al 2015). The most commonly employed reinforcement in aluminium matrix is silicon carbide (SiC) and alumina (Al2O3), as these materials exhibits greater hardness, tensile strength and impact strength in the homogenous composites and liquid metallurgy route is the most economical route for fabricating such homogenous composites (Singh et al 2012;Premnath et al 2014) in his investigation revealed that, the mechanical properties and adhesive wear behaviour of stir cast aluminium/Al2O3/graphite composite are found improved as the weight percentage of Al2O3 content increased. An increasing trend of hardness and impact strength with increase in SiC content has also been observed, as this is due to uniform distribution of SiC particles in the aluminium matrix (Singla et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The Archimedes method, which assumes that immersion in fluid can obtain the weight of a specimen, was used to detect the material density. The theoretical density of C93200 alloy composites were later obtained by applying the mixture formula [30] as given in Equation (1). ρth=1wmρm+wm1ρm1 where ρm and ρm1 represent the density of base alloy and density of marble and wm and wm1 represent the weight fraction of base alloy and marble respectively.…”
Section: Methodsmentioning
confidence: 99%